Uji Mutu Fisik Formula Shampo Ekstrak Sarang Semut (Myrmecodia Pendens) Sebagai Antiketombe - Ajeng Kurniati; Nur Aeni Hartih (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Dandruff is an anomalous state of the scalp one of the causes is the fungus Candida albicans. Ant nest (Mrymecodia pendens) is a natural material containing antifungal compounds namely flavanoid and tannin. The aim of this research is to make anti dandruff shampoo preparation form extract of ant nest (Myrmecodia pendens) with five variation concentration of 0%, 1,5%, 2%, 2,5% and 3%. The results show that ant nest extract (Myrmecodia pendens) can be formulated as an anti-dandruff shampoo that meets requirements such as organoleptic, pH, homogeneity, high foam, and foam stability.